Physisorption and Chemisorption Mechanisms Influencing Micro (Nano) Plastics-Organic Chemical Contaminants Interactions: A Review - Agboola, Omowumi D.; Benson, Nsikak U. (Frontiers in Environmental Science, 2021)
Plastic debris acting as sources and vectors for organic pollutants in both terrestrial and aquatic environments are increasingly becoming emerging micropollutants of enormous concern. This review article draws scientific publications to discuss inherent polymers commonly found in plastics and their affinity for different organic pollutants and composition, environmental factors, and features that contribute to variation in the sorption capacity of these synthetic plastics. This article also looks to outline the sorption mechanisms of organic contaminants to micro(nano)plastics (MNPs). The sorption capabilities of organic chemical contaminants to MNPs have been examined in terms of polymeric properties of plastics and environmental conditions. The review also examines the sorption mechanisms and dynamics behind plastic-organic contaminants interactions using kinetic and isothermal models. Furthermore, insights into future areas of research gaps have been highlighted.